Produção de significados a partir de investigações matemáticas: Função afim e contextos cotidianos - Sousa, Ivan Bezerra de (2018)
The use of new methodologies in the teaching of Mathematics is currently the subject of many discussions in this area. In the face of these searches for methodologies that can contribute to a better development of students. This research presents one of them, which deals with the study of mathematical investigations in the classroom in line with the theoretical model of semantic fields and, from this alliance, we propose the following general objective: to analyze productions of meanings in the study of related function, by means of investigative classes with contexts directed to the daily life. To this end, an activity elaborated on the sale of ice cream, which divided into three stages: the first one discussed this kind of entrepreneurship. In the second, it explored a table with the ingredients of nine flavors of ice cream. In the third stage, each team worked with a single flavor, with the purpose of creating strategies for the sales of this product, discovering the value of the cost of production, of the sales price and profit obtained with two different sizes of ice cream. Next, the objective of each team was to formulate the functions and the modeling of the graphs, based on the content of related function. Since this activity totally geared towards the production, sale and profit of ice cream, we devoted a good part of our discussions to the themes related to entrepreneurship, in which we bring a critical look on capitalism and neoliberalism for the improvement of our work. This research is qualitative, because it seeks to interpret and analyze the events that occurred during the teaching episodes. As for the data collection instruments, audio recordings, logbook annotations, written records of students, photographic records and application of questionnaires used. From the results obtained in the field research, a detailed analysis was made of the events of the eight encounters and the answers given by the students in each stage applied. From the analysis, it observed that meanings produced along the development of the activity. It was observed that the application of this intervention helped us to understand ideas about everyday contexts, contexts of teaching, detailed context, teaching of functions (mainly related function), mathematical investigations in the classroom and the theoretical model of the semantic fields, which were responsible for the reflections present here. This research evidences that the work with investigative classes and mathematical activities focused on everyday contexts favors new opportunities for students to develop and disseminate their mathematical ideas in the classroom.